How to prove that (2) is the fundamental solution (1)???

$\frac{\partial}{\partial x}\left(P\frac{\partial\varphi}{\partial x}\right)+\frac{\partial}{\partial y}\left(P\frac{\partial\varphi}{\partial y}\right)=0$ (1)

$\Phi=-\varphi_0\ln r+f$ (2)

$\varphi_0$ - solution of (1) ($\varphi_0(M,N)=1$ if $M=N$)

$f$ - belongs $C^{(2)}$ ($f(M,N)=0$ if $M=N$)

$r=\sqrt{(x-\xi)^2+(y-\eta)^2}$, $M(x,y)$, $N(\xi,\eta)$

(1) - Elliptic Equations

P.S. always possible to allocate the logarithm of the fundamental solutions of elliptic type?